2017
DOI: 10.1038/srep39786
|View full text |Cite
|
Sign up to set email alerts
|

Distinct prognostic values of S100 mRNA expression in breast cancer

Abstract: S100 family genes encode low molecular weight, acidic-Ca2+ binding proteins implicating in a wide spectrum of biological processes. S100 family contains at least 20 members, most of which are frequently dysregulated in human malignancies including breast cancer. However, the prognostic roles of each individual S100, especially the mRNA level, in breast cancer patients remain elusive. In the current study, we used “The Kaplan-Meier plotter” (KM plotter) database to investigate the prognostic values of S100 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 67 publications
7
58
0
Order By: Relevance
“…We saw a significant increase in CSF-2 expression in PyMT/p11-KO tumors but CSF-2 has not been shown to correlate with macrophage infiltration in breast tumors. We also observed a Previous gene expression studies showed that p11 correlated to poor overall survival in basal-like breast cancer (reviewed in (57). In elucidating the prognostic role of p11 in human breast cancer, we found that p11 mRNA was overexpressed in human breast tumors, correlated positively with overall survival and recurrence-free survival, and was increased in high grade tumors compared to low grade tumors and normal tissue.…”
Section: Discussionsupporting
confidence: 63%
“…We saw a significant increase in CSF-2 expression in PyMT/p11-KO tumors but CSF-2 has not been shown to correlate with macrophage infiltration in breast tumors. We also observed a Previous gene expression studies showed that p11 correlated to poor overall survival in basal-like breast cancer (reviewed in (57). In elucidating the prognostic role of p11 in human breast cancer, we found that p11 mRNA was overexpressed in human breast tumors, correlated positively with overall survival and recurrence-free survival, and was increased in high grade tumors compared to low grade tumors and normal tissue.…”
Section: Discussionsupporting
confidence: 63%
“…S100A6 expression has been associated with worse prognosis or the progression of several cancers including oncogynecology [50], colorectal [51], gastric [52], and renal [53]. In contrast, a recent study suggests a relation between S100A6 expression and better prognosis in breast cancer [54]. However, to the best of our knowledge, this is the first report in which the S100A family is described in saliva of bitches with mammary tumors.…”
Section: Discussionmentioning
confidence: 97%
“…It is additionally interesting to note that 14/18 of the upregulated protein-validated factors are associated with poor prognosis or invasion in breast cancers, when measured in serum or tissue; this suggests that cells which secrete these factors would have a negative impact on prognosis 39,41,47,49,54,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] . It is also of interest to note that in these studies 8/14 of these poorly prognostic factors have been seen to derive predominantly from stromal cells.…”
Section: Discussionmentioning
confidence: 99%